Competition between strain and dimensionality effects on the electronic phase transitions in NdNiO3 films - Wang, Le (2016)
Transition metal oxides host an array of exotic electronic phases, including superconductivity, ferroelectricity, quantum spin liquid and Mott insulators. Their extreme sensitivity to external stimuli enables various routes to manipulate the ground state, which greatly improves our understanding of the physics involved. Here, we report the competition between strain and dimensionality effects on the phase evolution in high quality NdNiO3 films down to several unit cells. While both compressive and tensile strains increase the Ni 3d band width and favor the metallic phase, reducing dimensionality, on the other hand, decreases the covalent band width and favors the insulating phase in NdNiO3. The experimental observations are well supported by ab initio calculations and improve our understanding of the electronic behavior in strongly correlated electron systems.